The Effect of The Imaginative Suggestion Method on Narrative Writing Skills of 6th Grade Students at Mandailing Natal - Yusnaleli, Yusnaleli; Rahmat Kartolo (International Journal of Educational Research Excellence, 2026)
This research was motivated by the low narrative writing skills of sixth-grade students at SD Negeri 012 Simangambat, which was indicated by a lack of creativity, completeness of content, and narrative structure in their writing. The conventional method, which mostly involved lecturing, proved insufficient to stimulate students’ imagination and interest in writing. This study used a quantitative approach with a quasi-experimental method. The sample consisted of two classes: the experimental class taught using the Imaginative Suggestion Method and the control class taught using conventional methods, each comprising 25 students (totaling 50 students). The primary instrument used was a narrative writing test based on indicators such as plot, content, organization, sentence structure, spelling, and punctuation. The data were analyzed using an independent samples t-test. The results showed that the average post-test score of students in the experimental class was 79.8, while the control class averaged 68.8. In the experimental class, 36% of students were in the "very good" category, 52% in the "good" category, and 12% in the "fair" category. Conversely, in the control class, only 12% were categorized as "very good," 52% as "good," and 36% as "fair." Hypothesis testing indicated that the calculated t-value (tₕ = 5.04) was greater than the critical t-value (tₜ = 2.01) at the 5% significance level, meaning H₀ was rejected and Hₐ was accepted. This implies a significant difference in the writing abilities of students taught using the Imaginative Suggestion Method compared to those taught conventionally. The strength of this method lies in its use of music to stimulate students’ emotional atmosphere and imagination, enabling them to express ideas and emotions more creatively in writing. Thus, it can be concluded that the Imaginative Suggestion Method has a positive and significant effect on improving the narrative writing skills of elementary school students.